2016
DOI: 10.1007/s11010-016-2907-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an RNA aptamer binding hTERT-derived peptide and inhibiting telomerase activity in MCF7 cells

Abstract: Human telomerase reverse transcriptase is an essential rate-limiting component of telomerase complex. hTERT protein in association with other proteins and the human telomerase RNA (hTR) shows telomerase activity, essential for maintaining genomic integrity in proliferating cells. hTERT binds hTR through a decapeptide located in the RID2 (RNA interactive domain 2) domain of N-terminal region. Since hTERT is essential for telomerase activity, inhibitors of hTERT are of great interest as potential anti-cancer age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The present study and Ming's study showed the similar potential effects of combined β-escin and 5-FU to reduce Bcl-2 protein expression, cell proliferation, and inducing cell apoptosis in SMMC-7721 and MCF7 cells with respect to untreated control cells or single treatment of 5-FU and β-escin. SMMC-7721 and MCF7 have different tissue origin; however, they have some similar properties such as positive telomerase activity[2930] which may be influenced in their response to the effects of combined β-escin and 5-FU. [31] It seems that the combination of β-escin and 5-FU may be effective, at least partly, on other cancer cell lines in special ratio and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The present study and Ming's study showed the similar potential effects of combined β-escin and 5-FU to reduce Bcl-2 protein expression, cell proliferation, and inducing cell apoptosis in SMMC-7721 and MCF7 cells with respect to untreated control cells or single treatment of 5-FU and β-escin. SMMC-7721 and MCF7 have different tissue origin; however, they have some similar properties such as positive telomerase activity[2930] which may be influenced in their response to the effects of combined β-escin and 5-FU. [31] It seems that the combination of β-escin and 5-FU may be effective, at least partly, on other cancer cell lines in special ratio and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivated aptazyme sensing hTERT included hTERT aptamer and hammerhead ribozyme. The sequence of hTERT aptamer or hammerhead ribozyme was shown in the previous studies (Chen et al, 2010;Varshney et al, 2017). The sequence of hTERT aptamer is 5'-AGACAAGAAUAAAACGCUCAAUAUUGG GCUUUUAGCUUCUUGGUUGGAUAAUAGAUACACAUU CGACAGGAGGCUCACAACAGGC-3'.…”
Section: Vector Constructionmentioning
confidence: 92%
“…Aptamers selected from SELEX further need structural and binding characterization and based on such analysis best aptamer candidates are selected for biochemical, functional and biological application. The final selected and characterized aptamers could be used for several applications [13,[37][38][39][40][41][42]. From the discovery of the first SELEX protocol till now, different types of SELEX have been established and merged with other advance technology based on their application in diverge fields [10,15,43,44].…”
Section: Systematic Evolution Of Ligands By Exponential Enrichment (Smentioning
confidence: 99%